2019
DOI: 10.1073/pnas.1902003116
|View full text |Cite
|
Sign up to set email alerts
|

Defining the layers of a sensory cilium with STORM and cryoelectron nanoscopy

Abstract: Primary cilia carry out numerous signaling and sensory functions, and defects in them, “ciliopathies,” cause a range of symptoms, including blindness. Understanding of their nanometer-scale ciliary substructures and their disruptions in ciliopathies has been hindered by limitations of conventional microscopic techniques. We have combined cryoelectron tomography, enhanced by subtomogram averaging, with superresolution stochastic optical reconstruction microscopy (STORM) to define subdomains within the light-sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 69 publications
0
49
0
Order By: Relevance
“…Interestingly, the tomograms also revealed a structure resembling the terminal plate found in motile cilia ( Figure 4A ). Super-resolution microscopy of immunolabeled proteins revealed concentric layering of the CC ( Figure 4B ) (Robichaux et al, 2019 ). Overlapping localization of IFT88, IFT81, and BBS5 distribution across CC was also observed ( Figure 4C ), suggestive of IFT trains.…”
Section: Structure Of the Photoreceptor Connecting Ciliummentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, the tomograms also revealed a structure resembling the terminal plate found in motile cilia ( Figure 4A ). Super-resolution microscopy of immunolabeled proteins revealed concentric layering of the CC ( Figure 4B ) (Robichaux et al, 2019 ). Overlapping localization of IFT88, IFT81, and BBS5 distribution across CC was also observed ( Figure 4C ), suggestive of IFT trains.…”
Section: Structure Of the Photoreceptor Connecting Ciliummentioning
confidence: 91%
“…Recent advances in super-resolution fluorescence microscopy and high-resolution cryo-TEM tomography have revealed detailed structure of the TZ and localized protein composition at nanometer resolution ( Figure 4 ) (Gilliam et al, 2012 ; Yang et al, 2015 , 2018 ; Shi et al, 2017 ; Robichaux et al, 2019 ; Sun et al, 2019 ). An elegant STORM-based study showed detailed localization of 12 distal appendage-associated molecules and 4 additional proteins surrounding the distal appendages (Yang et al, 2018 ) and super-resolution STED imaging mapped the distribution of TZ complex proteins in primary cilia (Yang et al, 2015 ).…”
Section: Structure Of the Photoreceptor Connecting Ciliummentioning
confidence: 99%
See 3 more Smart Citations